2009
DOI: 10.1002/art.24745
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐140 is expressed in differentiated human articular chondrocytes and modulates interleukin‐1 responses

Abstract: Osteoarthritis (OA) is a chronic and highly prevalent degenerative joint disease. Approximately 40 million Americans are currently affected, and this number is predicted to increase to 60 million within the next 20 years as a result of population aging and an increase in life expectancy (1,2). Current treatment is limited to pain management, and disease-modifying therapies are not available in the late phase of the disease process, at which point joint replacement surgery is often indicated. OA has been associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
341
2
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(376 citation statements)
references
References 41 publications
18
341
2
9
Order By: Relevance
“…Numerous miRNAs have been shown to be regulated by IL1b action (Miyaki et al 2009, Dai et al 2012, Matsukawa et al 2013. MMP13 is regulated directly by miR-27b and miR-127-5p (Akhtar et al 2010 or indirectly by miR-27a, miR-9, miR-488, or miR-22 (Iliopoulos et al 2008, Jones et al 2009, Tardif et al 2009, Song et al 2013b, among others.…”
Section: The Interplay Between Mirnas and Wnt/b-catenin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous miRNAs have been shown to be regulated by IL1b action (Miyaki et al 2009, Dai et al 2012, Matsukawa et al 2013. MMP13 is regulated directly by miR-27b and miR-127-5p (Akhtar et al 2010 or indirectly by miR-27a, miR-9, miR-488, or miR-22 (Iliopoulos et al 2008, Jones et al 2009, Tardif et al 2009, Song et al 2013b, among others.…”
Section: The Interplay Between Mirnas and Wnt/b-catenin Signalingmentioning
confidence: 99%
“…Besides its known role in chondrocyte differentiation, miR-140 also plays a central role in OA (Araldi & Schipani 2010). In vivo, miR-140 and miR-146a target ADAMTS5 (Miyaki et al 2009, Tardif et al 2009, while miR-125b targets ADAMTS4 (Matsukawa et al 2013). Moreover, miR-101 directly inhibits the expression of collagen type II and aggrecan genes through the downregulation of SOX9 expression (Dai et al 2012).…”
Section: The Interplay Between Mirnas and Wnt/b-catenin Signalingmentioning
confidence: 99%
“…Miyaki and colleagues (7) subsequently reported that deletion of this miRNA caused articular cartilage erosion in aged mice. They also reported elevated expression of miR-140 during chondrogenic differentiation from human mesenchymal stem cells (8). Work in our laboratory uncovered an abundant non-coding RNA transcript, H19, in healthy human articular chondrocytes (HACs) (9), which is processed to form a specific miRNA called miR-675 that positively regulates type II collagen, a critical component of articular cartilage (10).…”
mentioning
confidence: 95%
“…3 miRNA plays a key role in differentiation and growth in organs and tissues, 2 and miRNAs expressed specifically in cartilage [4][5][6][7][8] have been reported. Till date, miR21, 4 miR22, 9 miR27a, 6 miR140, 10 and miR146 8 have been reported as miRNAs that are associated with cartilage metabolism. Many studies have reported the use of a microarray analysis for isolating miRNAs that are expressed in a tissue-specific manner.…”
mentioning
confidence: 99%
“…Many studies have reported the use of a microarray analysis for isolating miRNAs that are expressed in a tissue-specific manner. For example, Miyaki et al 10 performed microarray analysis of MSC and articular chondrocytes, and they observed a high expression of miR140 in chondrocytes. They also observed the expression of miR-140 increased during chondrogenesis.…”
mentioning
confidence: 99%